AHCC®, a Standardized Extract of Cultured Lentinula Edodes Mycelia, Promotes the Anti-Tumor Effect of Dual Immune Checkpoint Blockade Effect in Murine Colon Cancer - Park, Hong-Jai; Boo, Sunjin; Park, Inkeun; Shin, Min Sun; Takahashi, Tsukasa; Takanari, Jun; Homma, Kohei; Kang, Insoo (Frontiers in Immunology, 2022)
Treatment strategies combining immune checkpoint blockade (ICB) with other agents have emerged as a promising approach in the treatment of cancers. AHCC®, a standardized extract of cultured Lentinula edodes mycelia, has been reported to inhibit tumor growth and enhance immune cell function. Here we investigated whether AHCC® promotes the therapeutic effect of immunotherapy in cancers. A combination of oral AHCC® and dual immune checkpoint blockade (DICB), including PD-1/CTLA-4 blockade, had reduced tumor growth and increased granzyme B and Ki-67 expression by tumor-infiltrating CD8+ T cells in MC38 colon cancer bearing mice compared to a combination of water and DICB. In the same tumor bearing mice, AHCC® and DICB treatment also altered the composition of the gut microbiome with the increased abundance of the species of Ruminococcaceae family which is associated with increased therapeutic efficacy of immunotherapy. The anti-tumor effect of AHCC® and DICB was not found in MC38 tumor-bearing mice treated with antibiotics. These data suggest that AHCC® increases the anti-tumor effect of DICB by enhancing T cell function and affecting the gut microbiome.